Zuojinwan ameliorates depressive-like behavior and gastrointestinal dysfunction in mice by modulating the FXR-bile acid-gut microbiota pathway - Qiao, Dan; Chen, Bo; Huang, Yuzhen; Su, Kunhan; Wu, Hao; Tao, Weiwei; Liu, Wanli (Frontiers in Microbiology, 2025)
Zuojinwan (ZJW), a traditional herbal formulation, is widely applied in the management of depression and gastrointestinal dysfunction. However, its underlying mechanisms remain inadequately characterized. This study investigated the antidepressant and gastrointestinal modulatory effects of ZJW via the bile acid–gut microbiota axis. A murine model exhibiting both depressive-like behavior and gastrointestinal disturbances was induced through chronic social defeat stress (CSDS). Antidepressant efficacy was evaluated using a battery of behavioral assessments, while gastrointestinal function was assessed by measuring total gastrointestinal transit time, colonic motility, gastric residual volume, and small intestine propulsion rate. Bile acid (BA) levels in the brain, gut, and serum were quantified using UPLC-MS/MS, and gut microbiota composition was analyzed via 16S rRNA sequencing. Histopathological examination and Western blotting (WB) were employed to assess tissue integrity and FXR protein expression, respectively. ZJW markedly ameliorated depressive behaviors and gastrointestinal dysfunction, concurrently mitigating intestinal and hippocampal neuronal damage. Treatment enhanced FXR expression, altered BA profiles, and enriched gut microbial diversity. Notably, co-treatment with the FXR inhibitor (Z)-Guggulsterone diminished the therapeutic effects of ZJW, underscoring the role of FXR signaling. These findings suggest that ZJW exerts its therapeutic benefits by activating FXR, modulating bile acid metabolism, and reshaping the gut microbiota.